El Núcleo de Apoyo Contable y Fiscal UNACH SRI y la generación de cultura tributaria en la ciudad de Riobamba, período 2021-2022. - Castañeda Guerrero, Kevin Eduardo (2023)
The present research work aimed to analyze the relationship between the UNACH SRI Accounting and Fiscal Support Center and the generation of tax culture in the students of the accounting and auditing career and the taxpayers of Riobamba City, period 2021-2022. The methodology used in the research was non-experimental and descriptive with a mixed correlational level approach. The methods, deductive and inductive, analytical, and statistical, were used with techniques such as surveys, interviews, and documentary observation to obtain relevant information. The results obtained identified that the level of tax culture of the taxpayers served by the NAF UNACH SRI improved in the year 2021; although most taxpayers demonstrated a high level of tax culture, there was a percentage that showed significant deficiencies. However, in 2022, a notable increase in the level of tax culture was observed, which indicates that the actions implemented have been effective in improving taxpayer knowledge, perception, and tax compliance. Likewise, it was possible to describe that the students of the Accounting and Auditing career linked to the NAF UNACH SRI show a significant increase in the level of tax knowledge, which is attributed to the training provided by the NAF, which focuses on two key indicators: formal duties and the regime for entrepreneurs and popular businesses (RIMPE), these efforts have allowed a greater percentage of students to obtain a high level of tax knowledge, going from 61.0% in 2021 to 72.5% in 2022. So, it was possible to affirm through Spearman's Rho correlation coefficient that there is a relationship between the UNACH SRI Accounting and Tax Support Center and the tax culture of the students and the taxpayers.